Effects of Nordic Walking Exercise on Body Mass Index and Waist Circumference Among Overweight Older Persons - ชัชวรัตน์ ลัชชี; ลาศุขะ ดวงฤดี; คำผลศิริ ทศพร (Nursing Journal CMU, 2019)
Overweight is defined as having more body fat, and results in chronic disease and health problems among older persons. Consistent practice of Nordic walking among older persons can reduce fat in the body. The objective of this experimental research was to examine the effects of Nordic walking on body mass index and waist circumference among overweight older persons. Subjects were 34 overweight older persons and were randomly assigned into the experimental and control group; 17 persons in the experimental group and 17 persons in the control group. Subjects in the experimental group participated in the Nordic walking exercise for 55 minutes a day, 3 days per week for 12 weeks, while those in the control group maintained their current exercise regimen. The instruments used in this study consisted of Nordic walking guidelines, a handbook on Nordic walking for overweight older persons, Nordic poles, a polar heart rate monitor, a data record form, a waist circumference measurement device and a bodyweight scale. Demographic data were analyzed using descriptive statistics and the hypotheses was tested using the t-test. The results of study showed that: The Body mass index of the experimental group after the Nordic walking regimen was significantly lower than before the regimen (p < .01). Body mass index in the experimental group after the Nordic walking regimen was significantly lower than that of the control group (p < .05). The waist circumference of the experimental group after the Nordic walking regimen was significantly lower than before the regimen (p < .001). The waist circumference of the experimental group after the Nordic walking regimen was significantly lower than that of the control group (p < .01).